De-democratization in Hungary: diffusely defective democracy. Issue 8 (17th November 2018) - Bogaards, Matthijs
ABSTRACT: Scholarly attention has started to shift from democratization and democratic consolidation to trends of democratic deconsolidation, backsliding, regression, and erosion. This article examines Hungary as a deviant and exemplary case for understanding de-democratization. The starting point is the literature on defective democracy, which provides a unified framework of analysis for the causes and the outcomes of democratization. However, as the case of Hungary shows, de-democratization is not simply the mirror of democratization. In Hungary, both the outcome and the process of de-democratization defy expectations. The democratic defects do not conform to any of the standard types, instead resembling a "diffusely defective democracy". Moreover, existing explanations fail to account for their emergence. The case of Hungary indicates that our knowledge of democratization may be a poor guide to understanding de-democratization.